The Construction of Tionghoa Ethnic Stereotype in Ngenest Movie - Sri Wijayati Wahid; Rhesa Zuhriya Briyan Pratiwi (Jurnal Ilmu Komunikasi, 2018)
Media, basically give a role in constructing second hand reality for audiences. Referring to the debates and stereotypes about ethnic and tribal issues, media became one of the contributing aspects. The emergence of stereotypes on the basis of generalization of assumption in a particular group tends to rise some mistakes, even on radically, it will lead into a conflict. Therefore, this research want to describe how the stereotypical construction of Chinese or Tionghoa ethnic in the packaging of comedy movie today, entitled Ngenest, by Ernest Prakasa. This light comedy genre film was also created and starred by Ernest Prakasa, recounted his life as an indigenous Tionghoa descendant who had to deal with social stereotypes of his Chinese. Through the analysis of critical discourse of Teun A. Van Dijk, this research give further analyzes in how the construction of reality towards Tionghoa ethnic stereotypes that raised in three basic aspects, i.e: text, cognitive, and social analysis.